2007
DOI: 10.1177/0961203307077560
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of panniculitis and haemophagocytic syndrome in a patient with chronic systemic lupus erythematosus

Abstract: Panniculitis rarely occurs in the course of systemic lupus erythematosus (SLE). When it occurs, it is thought to be mainly lupus erythematosus panniculitis (LEP). Here we describe a 32-year old Japanese woman with chronic SLE, who simultaneously presented facial lymphocytic lobular panniculitis and pancytopenia due to haemophagocytic syndrome. She showed several auto-antibodies against trilineage haematopoetic cells, an anti-cardiolipin antibody, and no evidence of viral infection, indicating that her haemopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Moreover, some other forms of panniculitis (e.g. systemic lupus erythematosus associated panniculitis, alpha‐l‐antirypsin deficiency panniculitis eosinophilic panniculitis, subcutaneous panniculitis‐like T‐cell lymphoma and cytophagic histiocytic panniculitis) have been reported (20–25). In fact, patients in this study were once diagnosed as lymphoid tuberculosis, recurrent abscess, soft tissue infection, pneumonia, haematosepsis, connective tissue disease, histiocytosis or even leukemia in local hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some other forms of panniculitis (e.g. systemic lupus erythematosus associated panniculitis, alpha‐l‐antirypsin deficiency panniculitis eosinophilic panniculitis, subcutaneous panniculitis‐like T‐cell lymphoma and cytophagic histiocytic panniculitis) have been reported (20–25). In fact, patients in this study were once diagnosed as lymphoid tuberculosis, recurrent abscess, soft tissue infection, pneumonia, haematosepsis, connective tissue disease, histiocytosis or even leukemia in local hospital.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that MAS may associate with both benign and malignant types of panniculitis, e.g. cytophagic histiocytic panniculitis, LEP and SPTCL [15, 16]. It may also develop as the onset or in the course of SLE, the incidence of such coexistence is about 0.9–4.6% [17, 18].…”
mentioning
confidence: 99%
“…There are various hypotheses concerning the exact pathogenesis of MAS and its possible concomitance with autoimmune disorders. As suggested by Deji et al , common antibody-mediated mechanisms might be responsible for both lymphocytic lobular panniculitis (as present in LEP) and hemophagocytic syndrome [16]. The other mechanisms taken into consideration in pathogenesis of reactive hemophagocytis in SLE are immune complex-mediated mechanisms and involvement of pro-inflammatory cytokines, however all those hypotheses require further studies [18].…”
mentioning
confidence: 99%